Caught in the Hinact: Crystal Structure and Spectroscopy Reveal a Sulfur Bound to the Active Site of an O2‐stable State of [FeFe] Hydrogenase. Issue 38 (23rd July 2020) - Rodríguez‐Maciá, Patricia; Galle, Lisa M.; Bjornsson, Ragnar; Lorent, Christian; Zebger, Ingo; Yoda, Yoshitaka; Cramer, Stephen P.; DeBeer, Serena; Span, Ingrid; Birrell, James A.
Abstract: [FeFe] hydrogenases are the most active H2 converting catalysts in nature, but their extreme oxygen sensitivity limits their use in technological applications. The [FeFe] hydrogenases from sulfate reducing bacteria can be purified in an O2 ‐stable state called Hinact . To date, the structure and mechanism of formation of Hinact remain unknown. Our 1.65 Å crystal structure of this state reveals a sulfur ligand bound to the open coordination site. Furthermore, in‐depth spectroscopic characterization by X‐ray absorption spectroscopy (XAS), nuclear resonance vibrational spectroscopy (NRVS), resonance Raman (RR) spectroscopy and infrared (IR) spectroscopy, together with hybrid quantum mechanical and molecular mechanical (QM/MM) calculations, provide detailed chemical insight into the Hinact state and its mechanism of formation. This may facilitate the design of O2 ‐stable hydrogenases and molecular catalysts. Abstract : Caught in the Hinact : [FeFe] hydrogenases are highly efficient catalysts for the interconversion of H2 and H + . However, they are highly O2 sensitive. Here, the X‐ray crystal structure of an O2 ‐stable state of [FeFe] hydrogenase, along with comprehensive spectroscopic analysis and molecular calculations reveals the presence of a sulfur ligand bound to the active site. These results provide crucial insight into O2 stability mechanisms in proteins.